Scientific Thinking and Metacognitive Monitoring of Students of Primary School Teaching - Nováková, Alena; Chytrý, Vlastimil; Říčan, Jaroslav (Scientia in educatione, 2018)
The research described in this article is focused on the analysis of the level of scientific thinking and the metacognitive monitoring of students of primary school teaching. The primary area of research is the use of the Lawson test of scientific reasoning extended by the self-evaluation scale, which can be used as an indicator of metacognitive monitoring. Based on the results of the given test, two indexes were computed: the absolute accuracy index (which determines the degree of accuracy of the subjective performance estimate compared to the objectively proven performance) and the bias index (which determines the degree of the individual’s underestimation or overestimation, i.e. the direction and size of errors in judgment). A total of 125 tests from student teachers were analyzed in order to establish the relationship between the results of the test of the level of scientific reasoning and the level of metacognitive monitoring. It has been found that students’ level of scientific reasoning shows a strong correlation in some areas with the self-assessment of the respondent (the better were the results of their tests of scientific reasoning, the more accurate the students were in assessing their own performance). The study also noted a difference in the level of scientific reasoning among former grammar school students who achieved a higher test score than those who studied another high school. All analyzed students tended to overestimate themselves, this trend does not vary depending on the type of high school studied.